Cell therapy for orofacial bone regeneration: A systematic review and meta‐analysis. (18th June 2019) - Shanbhag, Siddharth; Suliman, Salwa; Pandis, Nikolaos; Stavropoulos, Andreas; Sanz, Mariano; Mustafa, Kamal
Abstract: Aim: The objective of the present review was to answer the focused question: what is the effect of cell therapy in terms of orofacial bone regeneration compared to grafting with only biomaterial scaffolds and/or autogenous bone? Methods: Electronic databases were searched for relevant controlled clinical and pre‐clinical (large‐animal) studies. Separate meta‐analyses of quantitative data regarding histological or radiographic new bone formation were performed. Results: Forty‐seven eligible clinical and 57 pre‐clinical studies were included. Clinical studies were categorized based on the use of "minimally manipulated" whole tissues (e.g., bone marrow) or ex vivo expanded cells from "uncommitted" (bone marrow, adipose tissue) or "committed" sources (periosteum, bone). Based on limited and heterogeneous clinical evidence, implantation of cells (mostly whole bone marrow), in combination with biomaterial scaffolds results in bone regeneration which is (a) superior compared to implantation of scaffolds alone in sinus and horizontal ridge augmentation, and (b) comparable to autogenous bone in alveolar cleft repair. Conclusions: Although current evidence points to the benefits of cell therapy in certain clinical indications, it is unclear whether the use of ex vivo expanded cells, either uncommitted or committed, is superior to whole tissue fractions in terms of bone regeneration. The relatively larger effect sizes in favour of cell therapy observed in pre‐clinical studies are diminished in clinical trials. Future controlled studies should include cost‐effectiveness analyses to guide clinical decision‐making.